Towards a Global Understanding and Standardisation of Education and Training in Microsurgery - Clement Chi Ming Leung; Ali M Ghanem; Pierluigi Tos; Mihai Ionac; Stefan Froschauer; Simon R Myers (Archives of Plastic Surgery, 2013)
With an increasing emphasis on microsurgery skill acquisition through simulated training, the need has been identified for standardised training programmes in microsurgery. We have reviewed microsurgery training courses available across the six continents of the World. Data was collected of relevant published output from PubMed, MEDLINE (Ovid), and EMBASE (Ovid) searches, and from information available on the Internet of up to six established microsurgery course from each of the six continents of the World. Fellowships and courses that concentrate on flap harvesting rather than microsurgical techniques were excluded. We identified 27 centres offering 39 courses. Total course length ranged from 20 hours to 1,950 hours. Studenttoteacher ratios ranged from 2:1 to 8:1. Only twothirds of courses offered in-vivo animal models. Instructions in microvascular endtoend and endtoside anastomoses were common, but peripheral nerve repair or free groin flap transfer were not consistently offered. Methods of assessment ranged from no formal assessment, where an instructor monitored and gave instant feedback, through immediate assessment of patency and critique on quality of repair, to delayed reassessment of patency after a 12 to 24 hours period. Globally, training in microsurgery is heterogeneous, with variations primarily due to resource and regulation of animal experimentation. Despite some merit to diversity in curricula, there should be a global minimum standard for microsurgery training.